The Influence Of Technology Based Merdeka Curriculum On Student Haracter and Learning Motivationgrade IV SD - Abdullah, Astuti; Mulyadi, Mulyadi (ALENA : Journal of Elementary Education, 2025)
This study aims to determine how the implementation and influence of the technology-based Merdeka curriculum on the character and learning motivation of fourth-grade students at SDN 24 Batangase Maros. This type of research is ex post facto research using quantitative research methods. The population of this study was all fourth-grade students of SDN 24 Batangase Maros, totaling 49 students. The sample of this study was 24 class IV B students, 14 of whom were male students and 10 female students. The instruments used were questionnaires and documentation. The data analysis techniques used were descriptive and inferential analysis. The results of the study showed that: 1) The implementation of the technology-based Merdeka curriculum affects the character and learning motivation of students. This is realized by the use of projectors in the learning process so that students feel comfortable, more active and teachers do not dominate learning activities. And also able to shape students' character because in the process of implementing the Merdeka curriculum, the main focus is on instilling character values to produce a generation with good morals. 2) The technology-based merdeka curriculum has an effect on the character and learning motivation of students at SDN 24 Batangase Maros after obtaining the results of the hypothesis test with a significance value of 0.000 <0.05, meaning that there is an effect of using the technology-based merdeka curriculum on the character and learning motivation of student.